Os sentidos da crise financeira nos editoriais de CartaCapital e Veja: entre divergências discursivas, a disputa de um projeto para o Brasil - Silva, João Victor Borba Moura e (2013)
This dissertation aims at understanding the meanings which were built on the financial crisis in editorials by two weekly news magazines between September, 2008 and December, 2009. For that, we use French Discourse Analysis and its theoretical-methodological framework. As a theoretical basis needed for the application of Discourse Analysis, we use literature review on topics grounding the magazines' Discourses. Therefore, correlated topics, such as opinion journalism and the editorial, economics journalism and magazine journalism, the economic models from the past decades, the crisis in itself, and a history of the Conditions of Production in the aforementioned magazines are observed. As a methodological tool, we use the concept of Paraphrastic Families, which assist in identifying meanings and their arrangement in Discursive Formations. Reviewing such concepts allied to the Analysis leads to some conclusions regarding the meanings which are constructed by both magazines in this period so as to organise them into four Discursive Formations two of them found in both magazines, and the other two solely in either one of the magazines. Consistently with their history, reviewed in this work, CartaCapital built Keynesian meanings by severely criticising neoliberalism and by considering the return of a strong State as the solution for the crisis whereas Veja built neoliberal meanings by giving the crisis less importance, by overlooking the augmentation of the State, and by defending the neoliberal model even during such time. Both magazines reacted alarmingly when the crisis burst, which brings part of these publications' discourse closer to the report on the event as it is usual in informative journalism. Another Discursive Formation found in both magazines was an emergent discourse, from 'Lulism', social-economic formulation of diffusive character which has, because of its very nature, gained space in editorials so as to defend Brazil as a strong country in the midst of the crisis albeit the ideological differences between both magazines. Thereafter, we were able to establish the Ideological Formations by magazine. In CartaCapital, there is subordination of ideological regions to the seek for equality within capitalism. Whereas, in Veja, we found subordination of ideological regions to market freedom. Both magazines, nonetheless, try to mask their emergent 'Lulist' discourse with their premises. Understanding the way in which editorials by both magazines construct meanings about a crisis of great proportions helps to evaluate how they understand society and its identities inasmuch as those are the moments which lead to the limit of possibilities at stake in the discursive plane. Ergo, the topic studied here is relevant to the research strand 'Media and Contemporary Identities' in the Postgraduate Programme in Communications at the Federal University of Santa Maria inasmuch as it represents a study into the role of Media Communications in the construction of social dynamics.